Cover crops mitigate direct greenhouse gases balance but reduce drainage under climate change scenarios in temperate climate with dry summers. (8th March 2018) - Tribouillois, Hélène; Constantin, Julie; Justes, Eric
Abstract: Cover crops provide ecosystem services such as storing atmospheric carbon in soils after incorporation of their residues. Cover crops also influence soil water balance, which can be an issue in temperate climates with dry summers as for example in southern France and Europe. As a consequence, it is necessary to understand cover crops' long‐term influence on greenhouse gases (GHG) and water balances to assess their potential to mitigate climate change in arable cropping systems. We used the previously calibrated and validated soil–crop model STICS to simulate scenarios of cover crop introduction to assess their influence on rainfed and irrigated cropping systems and crop rotations distributed among five contrasted sites in southern France from 2007 to 2052. Our results showed that cover crops can improve mean direct GHG balance by 315 kg CO2 e ha −1  year −1 in the long term compared to that of bare soil. This was due mainly to an increase in carbon storage in the soil despite a slight increase in N2 O emissions which can be compensated by adapting fertilization. Cover crops also influence the water balance by reducing mean annual drainage by 20 mm/year but increasing mean annual evapotranspiration by 20 mm/year compared to those of bare soil. Using cover crops to improve the GHG balance may help to mitigate climate change by decreasing CO2 e emitted in cropping systems which can represent a decrease from 4.5% to 9% of annual GHG emissions of the French agriculture and forestry sector. However, if not well managed, they also could create water management issues in watersheds with shallow groundwater. Relationships between cover crop biomass and its influence on several variables such as drainage, carbon sequestration, and GHG emissions could be used to extend our results to other conditions to assess the cover crops' influence in a wider range of areas. Abstract : In the long‐term and under climate change scenarios, cover crops improve direct greenhouse gases balance compared to bare soil mostly due to an increase in carbon (C) sequestered in the soil. Cover crops influence the water balance by increasing evapotranspiration and decreasing water drainage. Cover crops' improvement of the greenhouse gases balance may help to mitigate climate change but their impact on water drainage could limit waterground recharge.